Representations of the additive group of a nuclear space in terms of self-adjoint operators - Lopotko, O. V. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
We prove theorems on integral representations of the additive group of a real nuclear space in terms of self-adjoint operators. We assume that algebraic relations are realized in a dense invariant set of integral vectors.